A practical guide to DNA metabarcoding for entomological ecologists. (30th December 2019) - Liu, Mingxin; Clarke, Laurence J.; Baker, Susan C.; Jordan, Gregory J.; Burridge, Christopher P.
Abstract : 1. DNA metabarcoding is a cost‐effective species identification approach with great potential to assist entomological ecologists. This review presents a practical guide to help entomological ecologists design their own DNA metabarcoding studies and ensure that sound ecological conclusions can be obtained. 2. The review considers approaches to field sampling, laboratory work, and bioinformatic analyses, with the aim of providing the background knowledge needed to make decisions at each step of a DNA metabarcoding workflow. 3. Although most conventional sampling methods can be adapted to DNA metabarcoding, this review highlights techniques that will ensure suitable DNA preservation during field sampling and laboratory storage. The review also calls for a greater understanding of the occurrence, transportation, and deposition of environmental DNA when applying DNA metabarcoding approaches for different ecosystems. 4. Accurate species detection with DNA metabarcoding needs to consider biases introduced during DNA extraction and PCR amplification, cross‐contamination resulting from inappropriate amplicon library preparation, and downstream bioinformatic analyses. Quantifying species abundance with DNA metabarcoding is in its infancy, yet recent studies demonstrate promise for estimating relative species abundance from DNA sequencing reads. 5. Given that bioinformatics is one of the biggest hurdles for researchers new to DNA metabarcoding, several useful graphical user interface programs are recommended for sequence data processing, and the application of emerging sequencing technologies is discussed. Abstract : This review summarises sampling methods for invertebrate DNA metabarcoding research, highlighting their characteristics that are pertinent to DNA metabarcoding, and providing some recommendation for entomologist end‐users. Sample handling procedures and molecular laboratory methods that can minimise bias during a conventional DNA metabarcoding workflow are described. Given that bioinformatics analyses can be daunting, useful graphical user interface programs are recommended here for entomologists to analyse their own DNA metabarcoding studies, as is the need to consult with bioinformatics experts.